KONDISI KIMIA TANAH PADA DUA LEVEL KETINGGIAN TEMPAT DI KAWASAN TAMAN NASIONAL LORE LINDU SULAWESI TENGAH - Umar, Husain; Yusran, Yusran; Mus’af, M. (Universitas Tadulako, 2019)
This study aims to determine the soil chemical conditions at two elevation levels in the Central Sulawesi Lore Lindu National Park area. This research was conducted for three months, November 2017 - January 2018, in the Lore Lindu National Park area, which is an altitude of 784.4 m and an altitude of 1697 m asl. This study used survey method, soil samples were collected at five points at a depth of 0-30 cm and then compiled into one sample. Soil samples were analyzed at the Soil Science Unit Laboratory, Faculty of Agriculture, Tadulako University. The results showed that soil chemical conditions at an altitude of 784.4 m asl were more fertile than the altitude level of 1697 m asll. The chemical conditions of the soil at an altitude level of 1697 m asl are pH (H2O 6.78), (KCl 4.44), C-Organic 1.53%, N-Total 0.10%, P-Available 14.32ppm, K-Available 18.18 (cmol (+) kg- 1, and CEC 16.42 V. While the chemical conditions of the soil at an altitude level of 784.4 m asl are pH (H2O 6.82), (KCl 4.58), C-Organic 2.16%, N-Total 0.14%, P-Available 15.43ppm, K -Available 12.44 (cmol (+) kg-1, and CEC 17.05 (cmol (+) kg-1.Keywords: soil chemistry, Lore Lindu National Park.